2022
DOI: 10.56369/tsaes.4155
|View full text |Cite
|
Sign up to set email alerts
|

PRODUCCIÓN DE GAS In vitro Y RESPUESTA PRODUCTIVA DE BECERRAS ALIMENTADAS CON UNA DIETA INTEGRAL QUE CONTIENE PASTA DE AJONJOLÍ (Sesamun indicum) COMO FUENTE PROTEICA

Abstract: <p><strong>Background.</strong> Given the production conditions in the resulting dry tropics, supplementation and use of protein sources is necessary. <strong>Objective.</strong> The objective of this study was to evaluate <em>in vitro</em> gas production, <em>in vitro</em> fermentation characteristics, productive response, ruminal characteristics, and apparent nutrient digestibility of a whole diet with sesame paste or soybean paste in calf feed. <stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 11 publications
(14 reference statements)
0
3
2
Order By: Relevance
“…Consequently, the digestibility of the evaluated treatments should record similar results, because DMD did not show differences (p0.05) between treatments (Table 3). In this study, the biogas production values for T2 were lower than those reported by García-Balbuena et al (2022), who carried out a research about a 10% sesame paste diet and recorded 117.02, 37.14, 18.10, and 172.32 mL g 1 DM, at 0-24 h, 24-48 h, 48-72 h, and 0-72 h, respectively. Methane production and DMD recorded higher values in T2 than those reported by García-Balbuena et al (2022) who obtained 30.39, 8.14, 4.86, 43.39, and 26.22 mL g 1 DM, at 0-24 h, 24-48 h, 48-72 h, 0-72 h, and DMD, respectively.…”
Section: Resultscontrasting
confidence: 75%
See 4 more Smart Citations
“…Consequently, the digestibility of the evaluated treatments should record similar results, because DMD did not show differences (p0.05) between treatments (Table 3). In this study, the biogas production values for T2 were lower than those reported by García-Balbuena et al (2022), who carried out a research about a 10% sesame paste diet and recorded 117.02, 37.14, 18.10, and 172.32 mL g 1 DM, at 0-24 h, 24-48 h, 48-72 h, and 0-72 h, respectively. Methane production and DMD recorded higher values in T2 than those reported by García-Balbuena et al (2022) who obtained 30.39, 8.14, 4.86, 43.39, and 26.22 mL g 1 DM, at 0-24 h, 24-48 h, 48-72 h, 0-72 h, and DMD, respectively.…”
Section: Resultscontrasting
confidence: 75%
“…Consequently, according to Cardona-Iglesias et al (2016), these variables fall within the optimal intervals for the induction of a fast growth of cellulolytic bacteria (Borroto, 2015): 6.2-7.0 pH and 1010 cells mL 1 ruminal bacteria, and 10 5 cell mL 1 protozoa concentrations. García-Balbuena et al (2022) reported a higher pH (7.47), bacteria (4.6710 9 cell mL 1 ) and protozoa (11.0210 5 cell mL 1 ) than this study. In addition, Carbajal-Márquez et al (2021) reported similar pH (6.6), bacteria (4.2710 9 cell mL 1 ), and protozoa (2.510 5 cell mL 1 ) values for Suiz-Bu calves that fed on Mulato II grass and were supplemented (1% of LW) with increasing levels of Earpod tree (Enterolobium cyclocarpum) pods.…”
Section: Resultscontrasting
confidence: 67%
See 3 more Smart Citations